Colorimetric-based Detection of TNT Explosives Using Functionalized Silica Nanoparticles. (2017) - Idros, Noorhayati; Ho, Man Yi; Pivnenko, Mike; Qasim, Malik M.; Xu, Hua; Gu, Zhongze; Chu, Daping
Abstract: This proof-of-concept study proposed a novel sensing technique for a label-free and selective detection of 2, 4, 6-trinitrotoluene (TNT) from 10 −12 to 10 −4 molar. Amine-terminated nanoparticles were used as TNT bioreceptors to form Meisenheimer complexes. A colorimetric change from green to red was observed after TNT functionalization, which caused by the increased in the nanoparticles separation. AptamerX was subsequently attached to confirm the sensing selectivity from 2, 4-dinitrotoluene control and baseline toluene. A combined effect of the peak wavelength shift of the reflected light normal to the film surface and the associated change of the peak width presents the merit function of this study.